W jakim stopniu seria podręczników „Elementy matematyki dla studentów ekonomii i zarządzania” wspomaga proces uczenia się matematyki wśród studentów pierwszego roku? - Zeug-Żebro, Katarzyna (To what extent a series of textbooks “Elements of mathematics for students of economics and management” supports the process of learning mathematics by first-year students?, 2011)
The construction of a mathematical textbook, in addition to such features as brevity, saturation of mathematical formulas and abstract reference in question, has several properties making its text characteristic. Factors determining the perception of such a text lie in its structure and in attitudes towards the recipients of the text. The study presents hidden views and opinions of students about the degree of suitability of a series of "Elements of mathematics for students of economics and management" and the difficulties of working with these books. For this purpose, a questionnaire among firstyear students of the University of Economics in Katowice was conducted. The study was conducted in two stages  in June 2007 and 2010
Didactics of Mathematics, 2011, Nr 8 (12), s. 135-140
Keywords: textbook of mathematics; functions of handbook